Immunopathogenesis of spondyloarthropathies – Concept of major histocompatibility locus-I-opathy - Amlan Kusum Datta; Uddalak Chakraborty; Swati Kumar; Atanu Chandra (Indian Journal of Rheumatology)
Spondyloarthropathies (SpA) are a group of overlapping disorders sharing certain common clinical features and genetic associations. Historically, most of the research into the pathogenesis of SpA and other types of chronic arthritis have conventionally focused on the adaptive immune system. However, recently, the pendulum has shifted in favor of innate immunity. With an aim to explore bridging concept of major histocompatibility locus (MHC)-I-opathy in context of immunopathogenesis of SpA, MEDLINE and PubMed (2000-2019) databases were searched for English language articles using keywords “MHC-I-opathy” and “spondyloarthropathy.” We reviewed papers which addressed the concept of overlap between innate and adaptive immunity and interplay between local tissue factors and innate cellular responses in the pathogenesis of SpA. The term “MHC-I-opathy” encompasses of a group of diseases which exhibit interaction between tissue-specific factors and innate immune cells. Further studies are needed for understanding of its therapeutic implication in such diseases.